Cobalt(I) and Nickel(II) Complexes of Bis(1, 3‐diphosphacyclobutadiene) Sandwich Anions1. Issue 5 (14th July 2015) - Rödl, Christian; Wolf, Robert
Abstract: Complexes [(C4 Me4 )Co(CO)2 {Co(P2 C2 t Bu2 )2 }] (1, C4 Me4 = tetramethylcyclobutadiene) and [CpNi{Co(P2 C2 t Bu2 )2 }(PPh3 )] (2, Cp = cyclopentadienyl) were synthesized by transmetalating [Tl(thf)2 {Co(P2 C2 t Bu2 )2 }] with [(C4 Me4 )Co(CO)2 I] and [CpNiBr(PPh3 )]. Compounds1 and2 were fully characterized by X‐ray crystallography, multinuclear NMR, UV/Vis, and IR spectroscopy, and elemental analysis. Their molecular structures show σ‐coordination of one phosphorus atom of the [Co(P2 C2 t Bu2 )2 ] – anion to the second metal atom (cobalt or nickel). Time‐dependent density functional theory (TD‐DFT) calculations were applied to gain insight into the electronic structures and the nature of the electronic transitions observed in the UV/Vis spectra. Cyclic voltammetry studies revealed the similar redox behavior of1 and2, which are reversibly oxidized to the corresponding monocations1 + and2 + with retention of the dinuclear structures. The cyclic voltammograms furthermore show that1 and2 decompose upon reduction with cleavage of the dinuclear structures into the free [Co(P2 C2 t Bu2 )2 ] – anion and further uncharacterized products. Abstract : Dinuclear diphosphacyclobutadiene complexes have been synthesized by transmetalating the thallium(I) salt [Tl(thf)2 {Co(P2 C2 t Bu2 )2 }] with organometallic cobalt(I) and nickel(II) halides. The structural, spectroscopic, and redox properties of two new bimetallic complexes are presented, and their electronic structures are analyzed by DFT calculations.